MODEL PEMBELAJARAN CHILDREN LEARNING IN SCIENCE (CLIS) TERHADAP KETERAMPILAN PROSES SAINS MATERI RANTAI MAKANAN - Izzah Khusma Awwalin; Reza Rachmadtulla (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by the low science process skills of students during learning. Many students are less active and do not pay attention to learning activities, so that learning outcomes are not optimal. The purpose of this study was to determine the effect of Children Learning In Science learning model on students' science process skills on food chain material. The method used was quasi experiment with posttest only control design. This study involved two groups, namely the experimental class using the Children Learning In Science model and the control class using conventional methods. Consisting of two classes, namely VA and VB SDN Keboananom Gedangan. The data collection method in this study was through tests. The results showed that the data were normally distributed and homogeneous based on normality and homogeneity tests. Hypothesis testing using t-test shows a significance value of (0.003, <0.005). This result proves that there is a significant effect of Children Learning In Science learning model on students' science process skills. In conclusion, the Children Learning In Science learning model can improve students' science process skills, especially in understanding food chain material. This model is effectively applied to create interactive, interesting, and meaningful learning, so it can be used as an alternative in improving the quality of learning.